Verificação do comportamento de ligações viga-pilar com continuidade de armadura negativa por meio de luvas rosqueadas - Barros, Luciana Souza Paes de (Universidade Federal de São Carlos, 2018)
Although an increasing demand on precast concrete structures exists, there is a lack of tools for the safe design of precast connections in many situations. This research focuses on the study of semi-rigid beam-column precast connections with continuity negative bars spliced by threaded couplers. Moment resistant connections using longitudinal reinforcement spliced by threaded couplers are common in Brazil but there are a few analytical models and experimental results describing such connections. The semi-rigid behavior of a beam-column connection is relative to its Moment-Rotation curve (M-θ). The secant rotational stiffness is associated to the point when the negative reinforcement starts yielding, which is related to the bond-slip between concrete and steel due to tension stresses in the cracked region. Two real scale cruciform tests are carried out in order to check the secant stiffness of beam-column connections Typology 3 and 4, as specified in ABNT NBR 9062:2017. The aim is to compare the experimental results with results obtained from analytical models presented in the aforementioned code. The behavior of negative threaded bars and the influence of the threaded couplers in the semi-rigidity of precast connections is discussed. The M-θ curves from both tests are presented and, considering the results of equivalent secant stiffness, it is proposed a calibration of the analytical parameters suggested in the Brazilian precast code. It can be noticed that the use of threaded couplers in beam-column connections satisfies design requirements of strength, stiffness and ductility, and that the Typology 4 of connection has a semi-rigid behavior. This research enables to observe that the tested typologies do not present a behavior of a discrete joint, so that the global, local and localized mechanisms interact with each other. For moment resistant connections subjected to negative flexure, its behavior is governed by the behavior of the negative continuity reinforcement, under small influence of the positive joint. Using analytical equations calibrated by test results, there are proper tools to the calculation of the negative secant stiffness and there is the possibility to manipulate equations and safely determine other parameters involved in the analysis and design of precast concrete structures.
Study of beam-column connections behavior using continuity negative bars spliced by threaded couplers
Keywords: Pré-moldado; Ligação viga-pilar; Rigidez; Rotação; Semirrígida; Luvas rosqueadas; Precast; Beam-column connections; Stiffness; Rotation; Semi-rigid; Threaded couplers; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS